Cellular toxicity of silicon carbide nanomaterials as a function of morphology. (October 2018) - Chen, Fang; Li, Gongyi; Zhao, Eric Ruike; Li, Jingting; Hableel, Ghanim; Lemaster, Jeanne E.; Bai, Yuting; Sen, George L.; Jokerst, Jesse V.
Abstract: Silicon carbide has been shown to be biocompatible and is used as a coating material for implanted medical devices to prevent biofilms. Silicon carbide nanomaterials are also promising in cell tracking due to their stable and strong luminescence, but more comprehensive studies of this material on the nanoscale are needed. Here, we studied the toxicity of silicon carbide nanomaterials on human mesenchymal stem cells in terms of metabolism, viability, adhesion, proliferation, migration, oxidative stress, and differentiation ability. We compared two different shapes and found that silicon carbide nanowires are toxic to human mesenchymal stem cells but not to cancer cell lines at the concentration of 0.1 mg/mL. Control silicon carbide nanoparticles were biocompatible to human mesenchymal stem cells at 0.1 mg/mL. We studied the potential mechanistic effect of silicon carbide nanowires on human mesenchymal stem cells' phenotype, cytokine secretion, and gene expression. These findings suggest that the toxic effect of silicon carbide nanomaterials to human mesenchymal stem cells are dependent on morphology. Graphical abstract: Image 1